Motivation and Job Performance among Nurses in the Health Tourism Hospital in Malaysia - Hee, Ong Choon; Kamaludin, Noor Hayati; Ping, Lim Lee (International Review of Management and Marketing, 2016)
In light of the increasing expectations of health travelers towards the quality of healthcare, this study intends to examine nurses' motivation and job performance in the health tourism hospital in Malaysia. Nurses were intended in this study because they represented majority of the workforce. The role of nurses is critical in patient's evaluation of their experience in the hospital. Administered on-site method was used to collect data from 180 respondents in a health tourism hospital. The finding of this study indicates that intrinsic motivation is positively and significantly related to nurses' job performance. The finding has prompted the hospital management to turn to intrinsic rewards instead of extrinsic rewards to motivate their nurses. Realistically, intrinsic rewards are less costly and more effective in enhancing nurses' performance. Career development, job enrichment and providing greater autonomy were among the ways to increase nurses' job performance. In addition, it is suggested that implementing interventions in terms of training, guidance and counselling would be able to produce motivated and high performance nurses in the hospital. This in return will fulfill the existing demands and expectations of the health travelers in Malaysia. Keywords: Job Performance, Intrinsic Motivation, Extrinsic Motivation, Nurses. JEL Classifications: J62, L83